Case Report: The Use of Herbal Medicine Lonicera and Forsythia as a Treatment of Bronchopneumonia in Cats - Nur Husodo, Tifano Pratista Ramandika; Putu Devi Jayanti; Putu Ayu Sisyawati Putriningsih (Universitas Airlangga, 2026)
Bronchopneumonia is a form of pneumonia that causes inflammation and infection in the respiratory tract (bronchi) and alveoli. Clinical studies show that Yin Qiao San has antibacterial and anti-inflammatory effects. This study aims to determine the Yin Qiao San herbal medicine as an alternative to the use of antibiotics for the treatment of bronchopneumonia in cats. The case animal named Bambam is a mixed-breed cat. The cat is a sterilized male, 3 years old, with a body weight of 3.75 kg. The cat had been sneezing for a month and was observed coughing several times. Physical examination revealed mucopurulent discharge and the presence of crackles. Hematology results indicated the cat had macrocytic hypochromic anemia. The presence of mucopurulent discharge raised suspicion of a bacterial infection. Discharge cytology revealed neutrophils, lymphocytes, and coccus bacteria, while bacterial culture identified Streptococcus sp. and Staphylococcus sp. The X-ray results showed ring-like shadows, tram lines, and air bronchograms. The cat was diagnosed with bronchopneumonia. Treatment involved the administration of herbal medicines Lonicera and Forsythia, given at a dose of one tablet twice daily, along with Livron B-Plex, one tablet once daily for 14 days. Therapy evaluation results showed clinical improvement, indicated by the absence of coughing and crackles, reduced nasal discharge, and decreased sneezing frequency. However, after treatment, the nasal discharge did not change, the discharge remained mucopurulent.